2008
DOI: 10.1152/ajplung.00338.2007
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte antibacterial functions are not impaired by perfluorocarbon exposure in vitro

Abstract: Application of liquid, aerosolized, and vaporized perfluorocarbons (PFC) in acute lung injury has shown anti-inflammatory effects. Although this may be beneficial in states of pulmonary hyperinflammation, it also could increase susceptibility to nosocomial lung infection. We hypothesized that PFC impair cellular host defense and therefore investigated in an in vitro model the influence of perfluorohexane (PFH) on crucial mechanisms of bacterial elimination in human neutrophils and monocytes. Using scanning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…27 When PFCs were used for in vitro labeling experiments, no negative effects were found on cell viability and cell function of dendritic cells 28 and polymorphonuclear neutrophils. 29 In summary, these current and other preliminary results of 19 F MRI applications for inflammation detection and the fact that the PFCs exhibit a high safety profile, [27][28][29] suggest a feasible and highly desirable transition of this 19 F approach into a clinical application. From a biological point of view, future studies are needed to test whether human macrophages are able to incorporate PFC in vivo in sufficient quantities to allow for noninvasive detection by 19 F-CMR.…”
Section: Clinical Perspective: Applications In Humansmentioning
confidence: 85%
“…27 When PFCs were used for in vitro labeling experiments, no negative effects were found on cell viability and cell function of dendritic cells 28 and polymorphonuclear neutrophils. 29 In summary, these current and other preliminary results of 19 F MRI applications for inflammation detection and the fact that the PFCs exhibit a high safety profile, [27][28][29] suggest a feasible and highly desirable transition of this 19 F approach into a clinical application. From a biological point of view, future studies are needed to test whether human macrophages are able to incorporate PFC in vivo in sufficient quantities to allow for noninvasive detection by 19 F-CMR.…”
Section: Clinical Perspective: Applications In Humansmentioning
confidence: 85%
“…Although the anti-inflammatory mechanisms of PFCs are not clear, most investigators initially considered that PFCs acted as a physical barrier on cell surfaces to prevent ligand-receptor-induced signal transduction and direct injury caused by inflammatory mediators [2][3][4]. Further investigations revealed that PFC particles were ingested early into phagocytic cells in a time-dependent manner, thus resulted in the formation of PFC-filled vacuoles [39]. Effect of FC-77 on MDA concentration and MPO activity in lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Only cells with PI-positive diploid DNA content (FL2, red fluorescence) were counted for the quantitative assay of phagocytosis activity. Data acquisition and analyses were performed using the CellQuest program (Becton Dickinson) for at least 1,000 monocytes and over 20,000 granulocytes [13,14].…”
Section: Analysis Of Phagocytosis Activitymentioning
confidence: 99%